Out of Pocket expenditure among beneficiaries of Janani Shishu Suraksha Karyakaram - Tyagi, Jyoti; Das, Jayanta K; Swain, Pushpanjali (Indian Journal of Community Health, 2016)
Background: About 67,000 women in India die every year (MoHFW, 2011), due to pregnancy related complications. Similarly, every year more than 13 lacs infants die, within 1 year of the birth and out of these approximately 9 lacs i.e. 2/3rd of the infant deaths take place within the first four weeks of life (1).Out of these, approximately 7 lacs i.e. 75% of the deaths take place within a week of the birth and a majority of these occur in the first two days after birth (1). In view of the difficulty being faced by the pregnant women and parents of sick new-born (MoHFW,2011), along with high out-of-pocket expenses incurred by them on delivery and treatment of sick new-born, Ministry of Health and Family Welfare has taken a major initiative, to provide completely free and cashless services to pregnant women including normal deliveries and caesarean operations and sick new born (up to 30 days after birth) in Government health institutions in both rural & urban areas. Material & Methods: In this community based descriptive cross-sectional study, data was collected from 100 mothers, who had delivered in last one year at District Hospital Maternal Wing situated at Morar Block of Gwalior District M.P and MO, ANM’s, ASHA’s, using Semi structured close ended Interview schedule and an open ended questionnaire respectively. Data were compared by using SPSS (ver. 22.0) Result: Expenses were divided under two heads, medical and non-medical. 15% of the total beneficiaries incurred the medical expenses in the form of medicines, diagnostics etc. and almost 99% of all the respondents incurred the non-medical expenses in the form of transport, food etc. Conclusion: Based on the outcome of the study the overall impression was that 59% of the beneficiaries were not aware of the JSSK scheme. Only during pregnancies through the initiatives of the ASHAs the beneficiaries came to know about the free entitlements of the scheme. There was unavailability of ambulance when required and delay in the services.